Sistem Informasi Manajemen Proyek Pembangunan PT. Tuffindo Investama Con - Fransiskus Daniel Chandra; Muhammad Rachmadi (Program Studi Sistem Informasi, Universitas Multi Data Palembang, 2023)
Technological developments cause all organizational and company actors to need information systems as a means of supporting operational activities. At PT. Tuffindo Investama Con, does not yet have an adequate system because it still uses a common system. The purpose of this research is to build a management information system that can assist the company in carrying out operational activities. The method used in this research is the RUP (Rational Undefined Process) method. At the inception stage, data collection and problem identification were carried out using interview and observation techniques. In the elaboration stage, problem analysis and needs analysis were carried out using PIECES analysis and cause and effect analysis. The construction stage is carried out by making applications and implementing application systems using class diagrams, activity diagrams and entity relationship diagrams. The programming language used is PHP and MySQL as the database server. The transition stage is carried out by testing the applications that have been made. The results of this study are expected to be able to build a project management information system that can help overcome the problems faced by PT. Tuffindo Investama Con and support daily operational activities, such as recording, project progress, calculations, and project transactions. Keywords: Information System, Project Management, RUP, MySQL, PHP